Evaluation on Service Coverage of Jatiwekas Water Treatment Plant of Tulungagung Regency Water Supply Company - Inka Muthia Ardhana; Taty Alfiah; Yonik Meilawati Yustiani (Journal of Community Based Environmental Engineering and Management, 2022)
Water Supply Company (WSC) of Tulungagung Regency uses treated water from the Jatiwekas WTP for distribution. Water Treatment Installation (WTI) Jatiwekas has three processing units, i.e., WTP with a capacity of 50 L/s (WTP 1), WTP with a capacity of 100 L/s (WTP 2), and WTP with a capacity of 40 L/s (WTP 3). The Jatiwekas WTP consists of flocculation, sedimentation, filtration, and reservoir. The objective of this study is to evaluate the WTP and calculate water demand by considering 90% service coverage. The research was conducted by field observations to obtain information. Based on SNI 6773:2008, most of the Jatiwekas WTP has met the requirements of the package type WTP, except for WTP 3 which has not met because its capacity exceeds the design of the WTP package unit, which only has a discharge rate of 1-50 L/s while the capacity of WTP 3 reaches 100 L /s. The Jatiwekas WTP does not meet the design criteria of the Directorate General of Public Works of Republic Indonesia, which states that the service coverage for small towns with a population of 20,000– 100,000 is 90%, to achieve 90% service coverage, the Jatiwekas WTP needs to increase water production capacity by 123.9 L/s.